PEMBERDAYAAN MASYARAKAT MELALUI USAHA BUDIDAYA IKAN KERAPU DI KABUPATEN PESISIR SELATAN (STUDI KASUS KELOMPOK NELAYAN KECAMATAN IV JURAI) - Intan Permatasari; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The phenomenon of low fishermen income, the Nipah River, IV Jurai Subdistrict which has the potential to cultivate grouper fish but limited human resources in managing the existing marine potential makes researchers interested in researching Community Empowerment through Grouper Cultivation Business in Pesisir Selatan Regency (Case Study). Fisherman Group of District IV Jurai). The purpose of this study was to determine community empowerment in grouper cultivation in Pesisir Selatan Regency and to determine the factors that hinder community empowerment through grouper cultivation in Pesisir Selatan Regency. This study uses a qualitative method where the data collection techniques used are interviews, observation and documentation. Data analysis techniques in this study are data reduction, data presentation and conclusions. The results of this study can be seen that community empowerment through grouper cultivation in Pesisir Selatan Regency on enabling indicators has been successful, but on empowering and protecting indicators it is still not successful, because there are several inhibiting factors, namely the lack of quality seed assistance from the Fisheries and Food Service. Pesisir Selatan Regency, the inability of some fishermen to manage capital, and the consumptive nature of fishermen. It is hoped that in the future the Fisheries and Food Service of Pesisir Selatan Regency will optimize the quality of the seed assistance provided, and also fishermen in IV Jurai District will be better at managing capital and eliminating consumptive nature.